분석단위 세분화에 따른 한강권역의 물수급 분석 비교 및 고찰 - 오지환; 김연수; 류경식; 배영대; Oh, Ji-Hwan; Kim, Yeon-Su; Ryu, Kyong Sik; Bae, Yeong Dae (Journal of Korea Water Resources Association, 2019)
Our country is making efforts to manage water resources efficiently. In the future, It is necessary to develop a plan after subdividing the basin considering regional problems and water use, topographical and climatic characteristics. This study constructed water supply and demand system based on the standard watershed unit for water shortage evaluation considering spatial resolution. In addition, water shortage were calculated and compared using the MODSIM model in the Han-river basin. As a result, the average water shortage occurring during the 49 years (1967-2015) was 129.98 million $m^3$ for the middle watershed unit and 222.24 million $m^3$ for the standard watershed unit, resulting in a difference of about 2.1 billion m3. However, the trends and distribution of water shortage occurrence were very similar. The reason for this is that, in the case of the Middle watershed unit analysis, water shortages are calculated for the demand for living, industrial, and agricultural water for the representative natural flow value, assuming that all the water can be used in basin. The standard basin unit analysis showed that the difference between the fractionated supply and demand resulted in a large water shortage due to the relatively small amount of available water, and that the main stream did not show water shortage due to the ripple effect of the return flow. If the actual water use system is considered in the model as well as the subdivision of the spatial unit, it will be possible to evaluate the water supply and demand reflecting the regional characteristics. 우리나라는 효율적인 수자원 관리를 위해 노력하고 있으며, 향후 지역의 문제와 물이용 현황, 특성, 지형, 기후 등을 고려한 유역을 세분화한 후 계획을 수립하는 것이 필요하다. 이에 본 연구에서는 한강 권역을 대상으로 MODSIM 모형을 활용하여 중권역과 표준유역단위 물 수급 체계를 구축하고 분석 결과를 비교하였다. 분석 결과, 49개년(1967-2015)간 발생하는 평균 물 부족량은 중권역 단위 129.98 백만$m^3$, 표준유역단위 2,229.24 백만 $m^3$으로 약 21 억$m^3$ 가량의 차이가 나타났으나 물 부족이 발생하는 시기와 물 부족 발생 공간 분포에 대한 경향은 매우 유사하게 나타났다. 이러한 원인은 중권역 단위 분석의 경우, 모든 수량을 이용할 수 있다는 가정으로 대표 자연유량 값에 대한 생활, 공업, 농업용수 수요량에 대한 물 부족량이 산정된다. 그러나, 표준유역단위 분석에서는 분할된 공급량과 수요량의 차이로 인해 본류와 이격되어 있는 지류는 가용할 수 있는 수자원량이 상대적으로 작아져 물 부족이 크게 발생하는 것으로 나타났고, 본류는 오히려 회귀수량의 파급효과로 인해 물 부족이 나타나지 않는 것으로 분석되었다. 향후, 분석 단위의 세분화 뿐만 아니라 실제 물이용체계가 모형 내 고려된다면 지역적 특성이 반영된 물수급 평가가 가능할 것으로 판단된다.